In the aftermath of earth, wind, and fire: natural disasters and respect for women’s rights - Detraz, Nicole (Human rights review, 2017)
Though much research has been devoted to a range of socioeconomic and political consequences of natural disasters, little is known about the possible gendered effects of disasters beyond the well-documented immediate effects on women’s physical well-being. This paper explores the extent to which natural disasters affect women’s economic and political rights in disaster-hit countries. We postulate that natural disasters are likely to contribute to the rise of systematic gendered discrimination by impairing state capacity for rights protection as well as instigating economic and political instability conducive to women’s rights violations. To substantiate the theoretical claims, we combine data on women’s economic and political rights with data on nine different natural disaster events—droughts, earthquakes, epidemics, extreme temperatures, floods, slides, volcanic eruptions, windstorms, and wildfires. Results from the data analysis for the years 1990–2011 suggest that natural disasters have a detrimental effect on the level of respect for both women’s economic and political rights. One major policy implication of our findings is that disasters could be detrimental to women’s status beyond the immediate effects on their personal livelihoods, and thus, policymakers, relief organizations, and donors should develop strategies to prevent gendered discrimination in the economy and political sphere in the affected countries.